2022
DOI: 10.1108/joepp-10-2021-0278
|View full text |Cite
|
Sign up to set email alerts
|

The link between workplace incivility, emotional exhaustion, and job embeddedness: examining the moderating role of power distance

Abstract: PurposeIntegrating the conservation of resources theory, Hofstede's national culture theory and the cognitive-motivational-relational theory of emotions, the authors propose that power distance (as a moderator) and emotional exhaustion (as a mediator) play a role in the relationship between workplace incivility, emotional exhaustion and job embeddedness.Design/methodology/approachThe data were collected in two stages using an online survey of 404 employees from three sectors, including hospitality, banking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
(132 reference statements)
1
0
0
Order By: Relevance
“…The positive correlation between nursing incivility and nurse stress aligns with previous research indicating that workplace incivility can lead to negative psychological outcomes and job dissatisfaction [ 71 75 ]. The findings here extend this understanding by quantifying the correlation and delineating the impact of different levels of incivility.…”
Section: Discussionsupporting
confidence: 86%
“…The positive correlation between nursing incivility and nurse stress aligns with previous research indicating that workplace incivility can lead to negative psychological outcomes and job dissatisfaction [ 71 75 ]. The findings here extend this understanding by quantifying the correlation and delineating the impact of different levels of incivility.…”
Section: Discussionsupporting
confidence: 86%
“…Experiencing workplace incivility negatively affect employee's mental health. This, in turn, can lead to non-work-related presenteeism if an employee is dealing with anxiety, depression, or other mental health challenges that affect their ability to focus on work and personal life (Gustiawan et al, 2023). Thus, present study found that workplace incivility is a strong predictor of the non-work related presenteeism, emphasizing the need of resolving uncivil workplace behavior.…”
Section: Relationship Between Work Incivility and Non-work-related Pr...mentioning
confidence: 51%
“…Additionally, given the current workloads and demands, the focus right now should be primarily on workplace stressors. Such pressures and strains greatly increase workplace conflict and severely lower employee morale (Gustiawan et al, 2023;Lin et al, 2023). Conflict results from the buildup of unfavourable feelings over time without an opportunity to let them go.…”
Section: Pharos International Journal Of Tourism and Hospitalitymentioning
confidence: 99%